2002
DOI: 10.1128/jvi.76.20.10290-10298.2002
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction and Transcription Factor Modification during Reactivation of Epstein-Barr Virus from Latency

Abstract: Reactivation of Epstein-Barr virus (EBV) from latency involves activation of theLatency and reactivation are defining features of herpesviruses, and several common human diseases are caused by their reactivation. Epstein-Barr virus (EBV) is particularly favorable for the study of reactivation because efficient reactivation can be induced in some Burkitt's lymphoma cell lines in response to physiologically relevant stimuli such as B-cell receptor (BCR) stimulation (38, 39) and cytokine treatment (3, 12). The ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
76
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 43 publications
(49 reference statements)
0
76
0
Order By: Relevance
“…Consistent with this, our results indicate that VPA significantly enhanced the luciferase activity derived from the Zp-luciferase construct even in the absence of a chromatinized template. Interestingly, one of the most important regulators of Zp transcription is the MEF-2D transcription factor, which is constitutively bound to the BZLF1 promoter but can serve either as a positive or negative regulator of BZLF1 transcription (47). When MEF-2D is complexed with HDAC proteins, it acts as negative regulator of transcription, and thus the ability of VPA to inhibit HDAC activity would be expected to convert MEF-2D bound to the BZLF1 promoter from a negative to a positive regulator of Zp transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our results indicate that VPA significantly enhanced the luciferase activity derived from the Zp-luciferase construct even in the absence of a chromatinized template. Interestingly, one of the most important regulators of Zp transcription is the MEF-2D transcription factor, which is constitutively bound to the BZLF1 promoter but can serve either as a positive or negative regulator of BZLF1 transcription (47). When MEF-2D is complexed with HDAC proteins, it acts as negative regulator of transcription, and thus the ability of VPA to inhibit HDAC activity would be expected to convert MEF-2D bound to the BZLF1 promoter from a negative to a positive regulator of Zp transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of chemotherapy to induce lytic EBV reactivation appears to require the simultaneous engagement of several different signal transduction pathways, including cellular stress MAP kinase p38, PI3 kinase, PKC delta, and ERK 1/2, but not cellular apoptosis per se (Feng et al, 2002a, and unpublished data). Interestingly, activation of these same cellular signal transduction pathways is also required for lytic EBV infection following engagement of the B-cell receptor (Adamson et al, 2000;Darr et al, 2001;Bryant and Farrell, 2002), suggesting that similar transcription factors may be involved. In addition, BRLF1-induced activation of the BZLF1 promoter requires the stress MAP kinases, p38 and c-jun Nterminal kinase, as well as PI3 kinase (Adamson et al, 2000;Darr et al, 2001).…”
Section: Activation Of Lytic Ebv Transcription By Modification Of Chrmentioning
confidence: 99%
“…In the case of the BZLF1 promoter (Zp), full activation Toxin expression specific to EBV-containing cells Figure 2 Latent viral promoters that require EBV-encoded gene products in trans, or the oriP replication origin that requires EBNA-1 in trans, can be used to produce cellular toxins specifically in EBV-positive cells requires both a 'ZII' motif (which binds CREB, ATF1, and a c-jun/ATF-2 heterodimer) and several different 'ZI' binding sites, which bind MEF2D as well as Sp1 and Sp3 (Flemington and Speck, 1990;Daibata et al, 1994;Speck et al, 1997;Wang et al, 1997;Adamson et al, 2000;Binne et al, 2002;Bryant and Farrell, 2002;Gruffat et al, 2002). Calcium-induced activation of MEF2D (mediated by calcineurin) and CREB (mediated by CaMKIV/GR) appears to be important for BZLF1 promoter activation following ligation of the B-cell receptor Liu et al, 1997).…”
Section: Induction Of Lytic Ebv Infectionmentioning
confidence: 99%
“…HDACs have been implicated in the regulation of latency of other herpesviruses, including Epstein Barr virus and human herpesvirus 8 (7,16). In addition, a recent study by Murphy et al (37) suggested that HDACs mediate repression of the CMV MIE promoter (MIEP) in nonpermissive cells because inhibition of HDACs induced viral permissiveness and increased MIEP activity.…”
mentioning
confidence: 99%